PENGEMBANGAN MEDIA GAMBAR PADA MATA PELAJARAN TEKNIK PENGAMBILAN GAMBAR DI KELAS X JURUSAN MULTIMEDIA SMK MANDIRI PONTIANAK - Suryatma, Indra; Aunurrahman, Aunurrahman; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe Purpose of this development research is to develop the image media on the subjects of image capturing techniques in improving student learning outcomes. The method of this research used is development method with descriptive qualitative approach. The subjects of the study were 29 students of the tenth graders. Techniques and data collection tools using; (1) expert validation questionnaire, (2) observation guide, (3) pretest and posttest. Data analysis using qualitative analysis. The results of the expert validation questionnaire validated and feasible to be used in research. Student learning outcomes measured through pretest and posttest of the basic techniques of capturing image are known; (l) pretest result shows 62.06 % of student unfinished while 37.93% student result of learning is complete, (2) result of posttest known 68.96% student result of learning complete and 31.03% student result of learning not complete. Learning by using the image media in image capturing technique subject to the students on the tenth graders in SMK Mardiri Pontianak, during the learning process conducted observations of student learning activities, the observation of student activity in learning activities known 82.75% students are very active and 17.24% of active students.Keywords: Image Media, Image Capturing Technique